Chemical and metabolomic screens identify novel biomarkers and antidotes for cyanide exposure. Issue 5 (23rd January 2013) - Nath, Anjali K.; Roberts, Lee D.; Liu, Yan; Mahon, Sari B.; Kim, Sonia; Ryu, Justine H.; Werdich, Andreas; Januzzi, James L.; Boss, Gerry R.; Rockwood, Gary A.; MacRae, Calum A.; Brenner, Matthew; et al.
Abstract : Exposure to cyanide causes a spectrum of cardiac, neurological, and metabolic dysfunctions that can be fatal. Improved cyanide antidotes are needed, but the ideal biological pathways to target are not known. To understand better the metabolic effects of cyanide and to discover novel cyanide antidotes, we developed a zebrafish model of cyanide exposure and scaled it for high‐throughput chemical screening. In a screen of 3120 small molecules, we discovered 4 novel antidotes that block cyanide toxicity. The most potent antidote was riboflavin. Metabolomic profiling of cyanide‐treated zebrafish revealed changes in bile acid and purine metabolism, most notably by an increase in inosine levels. Riboflavin normalizes many of the cyanide‐induced neurological and metabolic perturbations in zebrafish. The metabolic effects of cyanide observed in zebrafish were conserved in a rabbit model of cyanide toxicity. Further, humans treated with nitroprusside, a drug that releases nitric oxide and cyanide ions, display increased circulating bile acids and inosine. In summary, riboflavin may be a novel treatment for cyanide toxicity and prophylactic measure during nitroprusside treatment, inosine may serve as a biomarker of cyanide exposure, and metabolites in the bile acid and purine metabolism pathways may shed light on the pathways critical to reversing cyanide toxicity.—Nath, A. K., Roberts, L. D., Liu, Y., Mahon, S. B., Kim, S., Ryu, J. H., Werdich, A., Januzzi, J. L., Boss, G. R., Rockwood, G. A., MacRae, C. A., Brenner, M., Gerszten, R. E., Peterson, R. T. Chemical and metabolomic screens identify novel biomarkers and antidotes for cyanide exposure. FASEB J. 27, 1928–1938 (2013). www.fasebj.org